Pengaruh Norma HAM Terhadap Proses Kemerdekaan Timor Leste dari Indonesia - Ardli Johan Kusuma (Otoritas : Jurnal Ilmu Pemerintahan, 2017)
This paper discusses about the reasons of Indonesia which provides a referendum to East Timor which resulted in East Timor being independent from Indonesia. This paper is analytical descriptive, using qualitative methods, with the data collection techniques, using "librarian research" where data to support arguments are obtained by collecting such data from various sources such as books or literature, journals, newspapers, Magazines, as well as data sourced from the internet. The results of the discussion in this paper indicate the fact that the process of independence of Timor Leste from Indonesia because of the influence of human rights norms that at that time developed and became the international world agenda. So that, with using the human rights norms, Timor Leste and the international community succeeded in intervening in Indonesia to provide a referendum to Timor Lesete as the embodiment of human rights enforcement in Indonesia. Tulisan ini membahas tentang alasan Indonesia yang memberikan referendum kepada Timor Leste yang mengakibatkan Timor Leste merdeka dari Indonesia. Tulisan ini bersifat diskriptif analitis, dengan menggunakan metode kualitatif, dengan teknik pengumpulan data, menggunakan teknik librarian researchdimana data-data untuk mendukung argumen diperoleh dengan cara mengumpulkan data tersebut dari berbagai sumber seperti buku-buku atau literatur, jurnal, surat kabar, majalah, maupun data-data yang bersumber dari internet. Adapun hasil dari pembahasan dalam tulisan ini menunjukkan adanya fakta bahwa proses kemerdekaan Timor Leste dari Indonesia karena adanya pengaruh dari norma HAM yang saat itu berkembang dan menjadi agenda dunia internasinal. Sehingga dengan menggunakan norma HAM tersebut, Timor Leste bersama masyarakat internasional berhasil mengintervensi Indonesia untuk memberikan referendum kepada Timor Lesete sebagai perwujudan penegakan HAM di Indonesia.